ANALISIS PENGARUH TRADING VOLUME, MARKET VALUE, BIDASK SPREAD, TURNOVER DAN BOOK TO MARKET TERHADAP SPEED OF STOCK PRICE ADJUSTMENT (Studi Empirisi pada Perusahaan yang Terdaftar di Index LQ 45 Tahun 2013-2017) - Hadi, Naufal; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2019)
The aim of this study was conducted to test whether trading volume, market value, bid-ask spread, turnover and book to market of having an influence on the speed of adjustment in stock prices. The population in this study were 45 companies listed on the Indonesian Stock Exchange (BEI) in the year 2031 to 2017. The sampling technique in this research is purposive sampling method with criteria: 1) the company has been listed on the Stock Exchange as of 1 January 2013 until December 31, 2017, 2) the company's data did not have time to 'sleep' more than 15 days. Data obtained from the data which is provided by bloomberg. Multiple regression technique are chosen for this research statistic analysis. The results showed that the model was feasible based on the classical assumption. Technique of multiple linear regression analysis indicating that all independent variables have a significant influence on the dependent variable with a confidence level of 5 percent, except for the variable bid – ask spread and book to market that does not qualify as a variable that significantly influence the speed of stock price adjustments due to have a significance value above 5 percent.